Meningkatkan Keterampilan Menulis Bahasa Inggris melalui Teknik “Exposure Generalization Reinforcement and Use” - Kahidir, Muhammad (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2023)
In learning English, especially in the aspect of writing, which is attended by students with various levels of ability, it seems that they show less activity and mastery of grammar and vocabulary is still weak. This deficiency has an impact on the low learning outcomes of students’ writing in English. The purpose of this classroom action research is to improve students’ writing skills and improve mastery of sentence patterns and vocabulary in students’ English learning through the "Exposure Generalization Reinforcement And Use" technique in class X-2 students of SMA Negeri 1 Woja odd semester of the academic year 2022/2023. Based on the results of data analysis, the average value of the writing test in cycle I was 65.38, the average value of the writing test in cycle II was 70.83 and in cycle III was 74.84. In cycle I there were 56.41% of students classified as active and very active, in cycle II there were 97.44% of students classified as active and very active, while in cycle III all students seemed active. Based on the results of the research and discussion above, it can be concluded that the "Exposure Generalization Reinforcement And Use" technique can improve students’ English writing skills.